2021
DOI: 10.1093/mnras/stab1672
|View full text |Cite
|
Sign up to set email alerts
|

Stability of two-fluid partially ionized slow-mode shock fronts

Abstract: A magnetohydrodynamic (MHD) shock front can be unstable to the corrugation instability, which causes a perturbed shock front to become increasingly corrugated with time. An ideal MHD parallel shock (where the velocity and magnetic fields are aligned) is unconditionally unstable to the corrugation instability, whereas the ideal hydrodynamic (HD) counterpart is unconditionally stable. For a partially ionised medium (for example the solar chromosphere), both hydrodynamic and magnetohydrodynamic species coexist an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…However, here there are comparable numbers of fast and slow shocks in the system after 𝑡 = 0.8, and large un-corrugated coherent slow-mode shock structures exist in the simulation, see Figure 1b-d. A recent study has shown that the the corrugation instability can actually increase the number of detected shock pixels due to an increased shock length (Snow and Hillier, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, here there are comparable numbers of fast and slow shocks in the system after 𝑡 = 0.8, and large un-corrugated coherent slow-mode shock structures exist in the simulation, see Figure 1b-d. A recent study has shown that the the corrugation instability can actually increase the number of detected shock pixels due to an increased shock length (Snow and Hillier, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The Orszag-Tang vortex has been well studied in the literature (Dahlburg and Picone, 1989;Picone and Dahlburg, 1991;Jiang and Wu, 1999;Parashar et al, 2009;Uritsky et al, 2010). The initial conditions are evolved in 2D for ideal MHD equations using the 4th order central-difference solver in the (PIP) code (Hillier et al, 2016), which has been used previously to study shocks (e.g., Snow and Hillier, 2021). The simulations are performed using 1024 × 1024 cells with periodic boundary conditions.…”
Section: Mhd Simulationmentioning
confidence: 99%
“…Differently to the Orszag-Tang test presented earlier, the charged fluid might evolve similarly to the plasma in the MHD assumption, even if the collisional coupling is weak. A very demanding numerical experiment is the simulation of a perturbed 2D MHD slow shock front, leading in most of the cases to the corrugation instability (Stone & Edelman 1995;Snow & Hillier 2021). We use a background medium similar to that used by Snow & Hillier (2021) for parallel shocks.…”
Section: Corrugation Instabilitymentioning
confidence: 99%
“…A very demanding numerical experiment is the simulation of a perturbed 2D MHD slow shock front, leading in most of the cases to the corrugation instability (Stone & Edelman 1995;Snow & Hillier 2021). We use a background medium similar to that used by Snow & Hillier (2021) for parallel shocks. We use subscript 1 for downstream variables (x < 0) and subscript for 2 upstream variables (x > 0), where we exploit the frame of reference of the shock front, fixed at the location x = 0.…”
Section: Corrugation Instabilitymentioning
confidence: 99%
See 1 more Smart Citation